Consequences of screening in colorectal cancer (COS-CRC): development and dimensionality of a questionnaire - Jessica Malmqvist; Volkert Siersma; Christine Winther Bang; John Brodersen (BMC Psychology, 2021)
Abstract Background Harms of colorectal cancer (CRC) screening include psychosocial consequences. We have not identified studies using a participant-relevant questionnaire with adequate measurement properties to investigate these harms. However, Brodersen et al. have previously developed a core questionnaire consequences of screening (COS) for use in screening for life-threatening diseases. Therefore, the objectives were: (1) To investigate content validity of COS in a CRC screening setting and in case of gaps in content coverage (2) generate new items and themes and (3) test the possibly extended version of COS for dimensionality and differential item functioning (DIF) using Rasch Models. Methods We performed two-part-focus-groups with CRC screenees. Screenees were recruited by strategic sampling. In the first part 16 screenees with false-positive results (n = 7) and low-risk polyps (n = 9) were interviewed about their CRC screening experiences and in the second part COS was examined for content validity. When new information was developed in the focus groups, new items covering this topic were generated. Subsequently, new items were, together with COS, tested in the subsequent interviews. A random subsample (n = 410) from a longitudinal questionnaire study, not yet published, was used to form the data for this paper. We analysed multidimensionality and uniform DIF with Andersen’s conditional likelihood ratio test. We assessed individual item fit to the model. We also analysed Local Dependence (LD) and DIF by partial gamma coefficients using Rasch Models. Results COS was found relevant in a CRC screening setting. However, new information was discovered in the focus groups, covered by 18 new CRC screening-specific items. The Rasch analyses only revealed minor problems in the COS-scales. The 18 new items were distributed on four new CRC screening-specific dimensions and one single item. Conclusion An extended version of COS specifically for use in a CRC screening setting has been developed. The extended part encompasses four new scales and one new single item. The original COS with the CRC-screening specific extension is called consequences of screening in colorectal cancer (COS-CRC). COS-CRC possessed reliability, unidimensionality and invariant measurement.